id THE IMPACT OF BULLYING ON PSYCHO-SOCIAL EARLY CHILDHOOD - Ade Tursina; Rita Mahriza; Iqlima (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2022)
This study aims to determine the impact of bullying on children's psychosocial and provide education to parents about the risk of bullying for children's psychosocial development. This research used a qualitative method with a case study approach that is carried out in Tanjung Gelumpang Village, Kab. Aceh Tamiang. The subjects used were two children using interview and observation data collection techniques and then analyzed using the Milles and Huberman model consisting of data reduction, data presentation and conclusion drawing. The results showed that the impact of bullying caused the inhibition of children's psychosocial development such as the development of a child's guilt in doing anything, and having an attitude of not being able to realize the desires to be achieved, children not daring to adapt to their environment and not showing a sense of concern for others.